Enhancing Student Learning Motivation through Effective Management of Education and Educational Personnel at SMP Al-Amanah Cileunyi - EKA TRI OKTAVIANI; Pepen Supendi; Nia Rahmawati; Aura Vista (AIM: Journal of Islamic Education Management, 2025)
This qualitative study explores the influence of educator and educational personnel management on students’ learning motivation at SMP Al-Amanah Cileunyi, Bandung Regency. Using descriptive methods, data were gathered through observations, interviews with teachers, administrative staff, and students, as well as documentation analysis. The findings reveal that effective management of educators, particularly through structured training such as digital-based teaching, Canva, and Quizizz workshops, has enhanced instructional quality and student engagement. Teachers who apply innovative methods contribute significantly to increasing student motivation by making lessons more interactive and enjoyable. Additionally, the study highlights the vital role of educational personnel in supporting the learning environment. Administrative staff who ensure classroom cleanliness, timely availability of learning materials, and a well-maintained school atmosphere contribute to a more conducive space for learning. Students report higher enthusiasm and focus when learning environments are clean, organized, and supported with multimedia tools